REJUVENATION IN T.S. ELIOT’S THE WASTE LAND - Ahmed, Fatima Falih; Alshara, Moayad Ahmad (European Scientific Journal, ESJ, 2015)
Most of T.S. Eliot’s critics and readers see The Wasteland a poem about the crisis of modern culture, and the breakup of civilization. The poem has been discussed and analyzed according to this view. It is thought that the theme of the poem is that of the drifting barrenness in a world incapable of self-sacrificing devotion and no longer held by the bonds of love and faith. It is also thought that in the opening lines of the poem, spring and the promise of life are meant ironically. The study is an attempt to analyze the first part of the poem, "The Burial of the Dead" by which it becomes conspicuous that the poem is not totally about desperation and death. It could also be interpreted as a real promise of life and hope of resurrection. T. S. Eliot seems to be saying that out of death and winter come spring and new life. The opening of his poem portrays this concept clearly while the rest of the poem seems to briefly brush upon that notion, and the poem ends with an appeal for regeneration.